2005
DOI: 10.1152/ajprenal.00076.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes causes inhibition of glucose-6-phosphate dehydrogenase via activation of PKA, which contributes to oxidative stress in rat kidney cortex

Abstract: The incidence of diabetic nephropathy has been increasing. Studies have shown that oxidative stress (due to increased oxidant production and/or decreased antioxidant activity) is a critical underlying mechanism. The principal intracellular reductant is NADPH whose production is mainly dependent on glucose-6-phosphate dehydrogenase (G6PD) activity. Our work in cultured cells previously showed that high glucose caused activation of protein kinase A (PKA) and subsequent phosphorylation and inhibition of G6PD acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 45 publications
12
139
4
2
Order By: Relevance
“…The alloxan-diabetic rats evidenced significantly reduced G6PD activity and increased catalase activity. This decrease in G6PD activity in animal diabetic models has also been reported in other studies, and the activation of protein kinase A and subsequent phosphorylation and inhibition of G6PD has been proposed as the mechanism underlying this phenomenon (30). G6PD is the principal source of NADPH, on which the antioxidant system relies heavily.…”
Section: Discussionsupporting
confidence: 79%
“…The alloxan-diabetic rats evidenced significantly reduced G6PD activity and increased catalase activity. This decrease in G6PD activity in animal diabetic models has also been reported in other studies, and the activation of protein kinase A and subsequent phosphorylation and inhibition of G6PD has been proposed as the mechanism underlying this phenomenon (30). G6PD is the principal source of NADPH, on which the antioxidant system relies heavily.…”
Section: Discussionsupporting
confidence: 79%
“…In skeletal muscle cells, glycogenin mRNA expression was inhibited with increasing concentrations of cAMP [11], suggesting that diabetic nephropathy may therefore be associated with an inhibition of upstream cAMP-related pathways. While this is an attractive hypothesis, it does not agree with other studies that show increased cAMP and activated downstream signalling molecules such as cAMPdependent protein kinase in diabetic animals [12]. Treatment of diabetic animals with our new anti-fibrotic agent FT011 prevented the accumulation of Armanni-Ebstein lesions (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…To this end, it has been shown that the induction of diabetes in rats leads to a reduction in glucose-6-phosphate dehydrogenase (G6PD) and oxidative stress. 117 A reduction in G6PD activity leads to decreased NADPH and makes cells very sensitive to oxidant damage. 118,119 Deficiency in G6PD activity may lead not only to oxidative stress but also to nephropathy, as it has been shown that G6PD knockout mice have increased renal oxidative stress and elevated albuminuria.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%